Microstructure and corrosion resistance of laser powder bed fusion ODS-316L stainless steel - Qian Zheng; Yan Yin; Chao Lu; Zilin Li; Heng Zhu; Xiaoli Cui; Wenqing Shi; Xiao Liu; Ruihua Zhang; Di Tie (Journal of Materials Research and Technology, 2025)
Aiming at the development requirements for the cladding materials of the Generation-IV Supercritical Water-cooled Reactors (SCWR), this paper fabricated the oxide dispersion strengthened 316L stainless steel (ODS-316L) by laser powder bed fusion (LPBF) technology and systematically investigated the influence mechanisms of volumetric energy density on the densification behavior, microstructure evolution, and corrosion resistance. The research shows that the uniform dispersion of Y2O3 nanoparticles on the surface of 316L powder can be achieved by ball milling. Through the optimization of a wide range of laser power and scanning speed, ODS-316L components without defects such as pores and lack of fusion were obtained, and the highest relative density is close to 99.9 %. The addition of Y2O3 has no effect on the phase composition of the ODS-316L samples fabricated by LPBF. A typical fish-shaped molten pool and coarse columnar grains growing epitaxially along the <100> orientation are present in the ODS-316L alloys. The grain size of ODS-316L alloy achieves the minimum (103.6 μm) and the low-angle grain boundaries (LAGBs) reaches the maximum (57.1 %) at the volumetric energy density of 148.1 J/mm3. With the synergistic effect of grain size, LAGBs, and kernel average misorientation (KAM), the ODS-316L alloy exhibits excellent corrosion resistance in 3.5 wt% NaCl solution, i.e., the self-corrosion potential (Ecorr) increased to 0.103 V and the self-corrosion current density (Icorr) decreased to 1.737 × 10−8 A/cm2. A large number of nano Y–Si–O and Si–O oxide particles distributed at grain boundaries were found to be uniformly distributed in the matrix in the ODS-316L alloy prepared by LPBF, which facilitates grain refinement. This study provides a theoretical basis for the efficient fabrication of ODS alloys with complex structures for nuclear applications and a basis for optimizing the LPBF process strategy for fabricating ODS-316L.